Early-Life Exposure to Per- and Poly-Fluorinated Alkyl Substances and Growth, Adiposity, and Puberty in Children: A Systematic Review - Lee, Yun Jeong; Jung, Hae Woon; Kim, Hwa Young; Choi, Yoon-Jung; Lee, Young Ah (Frontiers in Endocrinology, 2021)
Per- or polyfluoroalkyl substances (PFAS), a family of synthetic polyfluorinated compounds, are widely used in consumer products. Ubiquitous exposures to PFAS, in consideration of their persistence, bioaccumulation potential, and toxicities have led to concerns regarding possible harmful effects during critical periods of development in early-life and long-term consequences on health. The potential effects of PFAS depend on various factors including the type of PFAS and the timing and level of exposure. We performed a systematic review of the epidemiologic literature to assess the effects of early-life PFAS exposure on prenatal and postnatal growth, adiposity, and puberty in children and adolescents. For birth size, most studies indicated that prenatal PFAS exposure, in particular long-chain PFAS, may impair fetal growth, albeit some reports of null associations with maternal PFAS. For growth within 2 years of age, prenatal PFAS exposure showed no associations with height and either null or negative associations with weight. However, postnatal PFAS exposures were inversely related to height and weight at 2 years in a cross-sectional study. For postnatal adiposity, prenatal PFAS may mostly have negative associations with body mass index in the first 2 years of life, but positive relationships with adiposity in childhood and adolescence, although some studies showed null associations. For puberty, the evidence for associations between early-life PFAS exposure and pubertal development or sex hormone levels were limited and inconclusive. From experimental studies, plausible mechanisms through which PFAS may affect early-life growth and puberty include PFAS-induced activation of peroxisome proliferator-activated receptor, alterations of thyroid or steroid hormone synthesis and metabolism, and their weak estrogenic or anti-androgenic properties. Although the published literature suggests possible effects of PFAS exposures on early-life growth, adiposity, and puberty, current human evidence is limited in establishing PFAS-induced effects on early-life physical development. Further investigation is warranted to clarify PFAS-induced effects on growth and physical development in consideration of the critical time-window of exposure, concomitant exposure to chemical mixtures including various PFAS types, and possible non-monotonic dose-response relationship for growth and adiposity trajectories.